Implementation of Telecommunications and Networks Through Business Communication - Junisa Fitri; Jhon Veri (SEAN Institute, 2025)
The purpose of this study is to find out the role of information and communication technology in business development. By using qualitative descriptive approach, the development of information and communication technology requires people to make changes in all kinds of lives whose goal is to get the best results. The development of information and communication technology, also has an impact on the form of trade that makes it easier to use. One of them is through e-commerce. Nevertheless, e-commerce has a very significant role, especially during the outbreak of Covid-19